2011
DOI: 10.1097/sle.0b013e31822f50b6
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Cause of Upper Gastrointestinal Bleeding

Abstract: Hemosuccus pancreaticus (HP) is a rare cause of upper gastrointestinal bleeding. Pancreatitis are the most common cause of HP. Here, we report the case of a 48-year-old male with HP due to alcohol-induced chronic pancreatitis. Superior mesenteric angiography showed an inferior pancreaticoduodenal artery pseudoaneurysm. The patient underwent coil embolization for treatment of his pseudoaneurysm. Endoscopic retrograde cholangiopancreatography and pancreatic stents replacement was performed for pancreatic pseudoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Bhasin et al [15] published their results with eight patients in 2013. Case reports from Elton et al (1997) included three patients and from Sayilir et al (2011) only one patient [16,17]. Earlier reports by Bhasin et al, Elton et al and Sayilir et al have shown promising results concerning the conservative treatment of bleeding PPCs with combining endoscopy and TAE [15][16][17].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Bhasin et al [15] published their results with eight patients in 2013. Case reports from Elton et al (1997) included three patients and from Sayilir et al (2011) only one patient [16,17]. Earlier reports by Bhasin et al, Elton et al and Sayilir et al have shown promising results concerning the conservative treatment of bleeding PPCs with combining endoscopy and TAE [15][16][17].…”
Section: Discussionmentioning
confidence: 98%
“…Case reports from Elton et al (1997) included three patients and from Sayilir et al (2011) only one patient [16,17]. Earlier reports by Bhasin et al, Elton et al and Sayilir et al have shown promising results concerning the conservative treatment of bleeding PPCs with combining endoscopy and TAE [15][16][17]. In their study on the efficacy of TAE in the treatment of PPAs in CP, Udd et al [4] performed therapeutic endoscopy following TAE on 13 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a connection with the digestive lumen is established, the patient will present an upper digestive bleeding with hematemesis and/or melena [5, 6]. Other rare possibilities are the exteriorization of the blood through the pancreatic duct and the ampulla of Vater resulting in “hemosuccus pancreaticus” [7, 8] and the development of a splenic hematoma [9]. …”
Section: Discussionmentioning
confidence: 99%
“…If the patient presents a stable hemodynamic status, endovascular approaches, placement of stents and/or embolisation, may be an elegant alternative to achieve hemostasis. In selected cases, endovascular and endoscopic approaches may be combined to solve both the vascular erosion and the cyst cavity [8, 12]. Open surgery is a solution if the patients present with hemodynamic instability and/or if the endovascular and endoscopic therapies are not available or have failed [11].…”
Section: Discussionmentioning
confidence: 99%